2015
DOI: 10.1063/1.4922244
|View full text |Cite
|
Sign up to set email alerts
|

Pre-breakdown processes in a dielectric fluid in inhomogeneous pulsed electric fields

Abstract: We consider the development of pre-breakdown cavitation nanopores appearing in the dielectric fluid under the influence of the electrostrictive stresses in the inhomogeneous pulsed electric field. It is shown that three characteristic regions can be distinguished near the needle electrode. In the first region, where the electric field gradient is greatest, the cavitation nanopores, occurring during the voltage nanosecond pulse, may grow to the size at which an electron accelerated by the field inside the pores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
0
26
1
Order By: Relevance
“…. Note that for the time of the order of tens of nanoseconds, pores can grow into much larger sizes (the rate of the expansion of nanopores is about 100-300 m/s [31,32]), but we disregard this fact for simplicity. If, in the process of growth, the size of the pores reaches the order of the laser wavelength, then the scattering ceases to be isotropic Rayleigh and becomes anisotropic Mie scattering (e.g.…”
Section: Rayleigh Scattering On the Cavitation Region Emerging In Liqmentioning
confidence: 99%
“…. Note that for the time of the order of tens of nanoseconds, pores can grow into much larger sizes (the rate of the expansion of nanopores is about 100-300 m/s [31,32]), but we disregard this fact for simplicity. If, in the process of growth, the size of the pores reaches the order of the laser wavelength, then the scattering ceases to be isotropic Rayleigh and becomes anisotropic Mie scattering (e.g.…”
Section: Rayleigh Scattering On the Cavitation Region Emerging In Liqmentioning
confidence: 99%
“…It is seen that the pore in water as well as in transformer oil is stretched along the electric field, since the pressure at its poles is greater than the pressure at the equator. In the approximation of a spherical pore, from the equations (1) and (2) and after averaging over the angle of all the forces acting on the surface, we obtain the equation for the radius of the expanding pores [28]: It can be seen that the rate of expansion of the pores reaches hundreds of meters per second, which on one hand they are almost by two orders of magnitude greater than the velocity of the fluid near the electrode [19], but on the other they are much smaller than the velocity of sound and reach the size of about 10 nanometers within a few hundreds of nanoseconds. Thus, for accepted values of "external" field 0 E , the potential difference at the poles of pores reaches or exceeds the ionization potential, at 5 ≈ R and at 14 nm, for water and oil, respectively.…”
Section: Estimation Of the Rate Of The Nanopores Expansionmentioning
confidence: 99%
“…In the paper [28], the estimate of the rate of the nanopores expansion is made, and it was shown that three characteristic regions are arising in the vicinity of a needle electrode. In the first region, where the electric field gradient is the greatest, the occurring cavitation nanopores have enough time to grow to a size at which an electron can gain enough energy for the excitation and ionization of the liquid molecules on the pore wall.…”
Section: Introductionmentioning
confidence: 99%
“…A method to determine the critical parameters at which cavitation begins on the basis of the comparison between the experiment and the simulation results within the framework of hydrodynamics of compressible fluids was also proposed. The theory of nanopore generation and expansion in fluids under the influence of nanosecond pulsed electric fields was proposed and developed in [15,16].This paper shows that the Rayleigh scattering off nanopores, emerging from the negative pressure regions of the liquid, can be used to detect cavities earlier in their development than other optical methods.…”
mentioning
confidence: 99%
“…It was shown in [15,16] that the average negative pressure acting on the surface of spherical nanopores in the vicinity of a needle-like electrode in water is:…”
mentioning
confidence: 99%